The Philosophy of Bead Colors among the Dayak Kenyah in North Samarinda - Mubarak, Zakiyyah Jadidah; Maulina, Rini; Wahdiniwaty, Rahma (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Cultural values of the Dayak Kenyah people are manifested in beads and their specific colors in daily socio-religious life, including the colors’ philosophy which is prone to change due to modernization. This study focuses on documenting and analyzing such philosophy to maintain the Dayak Kenyah’s identity. Employing a qualitative approach, data were collected through interviews and documents and analyzed using an interactive analysis model, including data reduction, data presentation, and conclusion drawing. The findings reveal five dominant colors: yellow (majesty and sacredness), red (bravery and fighting spirit), green (fertility and harmony between humans and  environment), white (purity), and black (protection, steadfastness, and spiritual depth). These colors function as cultural symbols representing the Dayak Kenyah’s life values. This research is expected to further preserve national cultural heritages, strengthen local cultural identity, and serve as a reference for the development of ethnoaesthetic documentation and policies for the protection of indigenous cultures in Indonesia.